Analisis Efisiensi Pemasaran Usaha Purse Seine di Kota Ambon - Lilian Mathilda Soukotta (Jurnal Wilayah dan Lingkungan, 2015)
The purpose of this research is to evaluate marketing efficiency by using structure, behavior, and market performance approaches of the purseseine catch in Ambon city. The data collected from the purse seine owners and fish traders cover the market integration and price transmission elasticity. The analysis of market structure and behavior are used to depicting the market performance occurred in the fish market of Ambon city. The results show that (1) market integration is absent due to oligopsony practice; (2) market behavior varies where the retailers immediately increase the fish price if the market price is sharply increasing, and they are reluctant to reduce the price if the fish price is decreasing; (3) for each market location, the number of retailersis fewer than the producers, the barriers to entry for both the producers and retailers is absent; and the fresh marketed fish has a similar quality except under the condition where the abundant fish stored in the cold storage for the next day trading.